Pemphigoid gestationis – a rare dermatosis of the prenatal period. Case report - Skutil, Marcin M.; Roztoczyński, Ryszard (Dermatology Review/Przegląd Dermatologiczny, 2016)
Introduction. Most skin lesions during pregnancy are associated with hormonal changes. Pemphigoid (herpes) gestationis (PG) is a significant dermatosis of the prenatal period reflecting pathology affecting the mother and fetus. Objective. The aim of the study was to present a PG case, a rare pregnancy dermatosis with a severe clinical outcome during the postpartum period. Case report . We present a case of a patient in whom skin lesions with tense blisters occurred at the 40th week of pregnancy. Herpes gestationis – a rare skin disease – was diagnosed based on the clinical picture. During the first days of puerperium, because of an aggressive disease course, the patient was transferred to a reference centre for skin disease treatment. She was given corticosteroid therapy, which brought the expected results. Conclusions. Pemphigoid gestationis is a rare and serious dermatosis of the prenatal period. Although the treatment of such diseases is the dermatologists’ task, obstetricians are responsible for diagnosis and for fetal monitoring considering placental pathology.